Biosecurity in Putin's Russia - Zilinskas, Raymond A.; Mauger, Philippe, 1991- (Lynne Rienner Publishers, Inc., 2018)
In March 2012, at a meeting convened by the recently reelected Russian president Vladimir Putin, Minister of Defense Serdyukov informed Mr. Putin that a plan was being prepared for ""the development of weapons based on new physical principles: radiation, geophysical wave, genetic, psychophysical, etc."" Subsequently, in response to concerns expressed both in Russia and abroad, the Russian government deleted the statement from the public transcript of the meeting. But the question remains: Is Russia developing an offensive biological warfare program? Raymond Zilinskas and Philippe Mauger invest.